2017
DOI: 10.1152/ajpcell.00027.2017
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of S1P3 receptor protects mouse soleus from age-related drop in muscle mass, force, and regenerative capacity

Abstract: We investigated the effects of S1P deficiency on the age-related atrophy, decline in force, and regenerative capacity of soleus muscle from 23-mo-old male (old) mice. Compared with muscle from 5-mo-old (adult) mice, soleus mass and muscle fiber cross-sectional area (CSA) in old wild-type mice were reduced by ~26% and 24%, respectively. By contrast, the mass and fiber CSA of soleus muscle in old S1P-null mice were comparable to those of adult muscle. Moreover, in soleus muscle of wild-type mice, twitch and teta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 66 publications
(117 reference statements)
0
13
0
Order By: Relevance
“…Our group, and others, contributed to clarify the role of the bioactive S1P in SkM cell biology, showing its role as pro-survival and myogenic factor [13,[51][52][53][54]. The capability of S1P to also modulate SkM phenotype has been also documented in vivo and ex-vivo/in vitro by our group and others [17,26,55]. Compared with SphK, the information regarding the involvement of CerK and its product C1P in SkM phenotype is limited.…”
Section: Discussionmentioning
confidence: 94%
“…Our group, and others, contributed to clarify the role of the bioactive S1P in SkM cell biology, showing its role as pro-survival and myogenic factor [13,[51][52][53][54]. The capability of S1P to also modulate SkM phenotype has been also documented in vivo and ex-vivo/in vitro by our group and others [17,26,55]. Compared with SphK, the information regarding the involvement of CerK and its product C1P in SkM phenotype is limited.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, the increased level of the two atrophy‐specific E3 ubiquitin ligases, atrogin‐1 and MuRF1, and of the autophagic marker, p62, and the LC3II/I ratio indicate that S1P deprivation induces activation of the atrophy/autophagy process and explains the reduced mean fibre CSA of the antibody‐treated mdx soleus. It is possible that S1P might exert its trophic effects directly on the muscle and/or indirectly through the neuromuscular junction (Bondì et al., 2017; Zanin et al., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Soleus muscle regeneration was induced by notexin as previously published (Bondì et al., 2017). Acute degeneration was induced in the left soleus by injecting, through a small cutaneous incision, 0.075 ml of the myotoxic drug notexin (0.5%; Sigma, St Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Bondì et al [128] observed that S1P/S1PR3 axis plays a negative role in muscle mass maintenance and force in soleus during aging and extracellular S1P exerts a protective effect during muscle fatigue development [129]. S1P/S1PR3 signaling also modulates excitation-contraction coupling and intracellular calcium mobilization [121][122][123][124][125][126][127][128][129][130].…”
Section: S1pr In Skeletal Muscle Systemmentioning
confidence: 99%